ANALISIS ANOMALI PASAR MODAL DI INDONESIA (Studi Kasus Indeks LQ 45, Indeks Sektor Konsumsi Dan Indeks Sektor Keuangan Tahun 2014-2016) - Desyanti, Vika Aristia (Jurnal Ilmiah Mahasiswa FEB, 2017)
Based on the efficient market hypothesis, investors should not be able to benefit more than average (abnormal returns) in predicting the rate of return of a stock. This is contrary to the hypothesis that the events market anomalies that were not anticipated and which give investors the opportunity to earn abnormal return.. This research testing aboutÂ  Eid al fitr holiday effect, school year seasional effect, day of the week effects and the turn of the month effect on stock returns index LQ 45 index, Index Consumption Sector and Financial Sector Index in 2014-2016. Using Paired Samples T Test or Wilcoxon Test to prove capital market anomalies in the Indonesia. The results showed a seasonal anomaly does not occur Eid al fitr holiday effect, School year seasional effect, effect Monday, the weekend effect on index LQ 45, Sector Index Consumption and Financial Sector Index in 2014-2016, as well as not occurred turn of the month effect on LQ 45 and consumption Sector Index. But the turn of the month effect occurs Financial Sector Index 2014-2016 year.Â Keyword : Capital market anomalies, , ied al fitr effect, school year seasional effect, day of the week effect and turn of the month effect